What's Yours Is Mine : Against the Sharing Economy. - Slee, Tom, 1959- (OR Books, 2016)
"The news is full of their names, supposedly the vanguard of a rethinking of capitalism. Lyft, Airbnb, Taskrabbit, Uber, and many more companies have a mandate of disruption and upending the "old order"--And they've succeeded in effecting the "biggest change in the American workforce in over a century," according to former Secretary of Labor Robert Reich. But this new wave of technology companies is funded and steered by very old-school venture capitalists. And in What's Yours Is Mine, technologist Tom Slee argues the so-called sharing economy damages development, extends harsh free-market practices into previously protected areas of our lives, and presents the opportunity for a few people to make fortunes by damaging communities and pushing vulnerable individuals to take on unsustainable risk. Drawing on original empirical research, Slee shows that the friendly language of sharing, trust, and community masks a darker reality."--